Nutritional status of liver transplant candidates - Sökülmez Kaya, Pınar (Progress in Nutrition, 2017)
Aim: The aim of the present study was to determine nutritional status, food consumption frequency, and malnutrition rate of the patients on the waiting list for liver transplantation as nutrition has high risk in such patients. Method: In this, study nutritional status of a total of 102 liver transplant candidates, 41 women and 61 men, was evaluated. Data on anthropometric measurements, frequency of food consumption and eating habits of the patients was collected via a survey. Obtained data was recorded and expressed on computers using the SPSS 13.3 package program. Results: The average weight and height of the patients on the waiting list for liver transplantation was 78.5±15.5 kg (81.81±52.33 kg for men; 73.6±38.89 kg for women) and 1.66±0.92 m (170.66±26.78 cm for men; 158.32±19.79 cm for women), respectively. Considering their BMI, 37.6% of patients were found overweight and 37.6% were obese. According to SDG results, 28.4% (n=29) of the patients had moderate Protein-Energy Malnutrition (PEM). 76.5% of the patients skipped meals and 53.9% of those skipped meals as they had distaste at eating. While 12.7% of patients did not eat anything when they were tired or sad, 41.2% ate less than ever. 75.5% of the patients consume salty/ low-sodium food. Conclusion: Obesity may be as threatening as malnutrition for patients with chronic liver disease. Therefore, nutritional status- one of the variables affecting morbidity and mortality of liver transplantation candidatesshould be well monitored, and changes should be made when necessary.